Perceptions in the mental health of pregnant women during the Covid-19 pandemic (Research, Society and Development, 2021)
Objective: to identify the main psychological aggravations caused by pregnant women during the isolation of the Covid-19 pandemic. Methodology: this is an integrative literature review (RIL), using as the database available in full Scielo, Pubmed and Lilacs. Subsequently, an analysis and a qualitative study of the articles found was carried out, with only 13 articles being selected to compose the research, according to the norms. Results: The mental health of pregnant women was significantly impaired during the pandemic phase, causing anxiety, fear, stress, apprehension and feelings of loneliness. Findings that have been observed in different locations around the world. There was a significant improvement in women who had family support and who were better observed during their consultations by professionals. Conclusion: the psychological adversities that pregnant women faced during the pandemic that must be taken into account are: increasing the quality of care provided by all professionals, generating essential social support in times of crisis.